Timing, Source, and Placement of Nitrogen Fertilizer Increases Wheat Yield and Protein Content in High Yielding Environments - L. M. Simão; D. A. Ruiz Diaz; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2021)
The efficiency of nitrogen (N) fertilizer management depends on rate, timing, placement, and source, but the benefits of an integrated program have not been clearly quantified, to our knowledge. This study aimed to investigate the effects of integrated N management on winter wheat grain yield, grain protein content, grain test weight, and biomass in Kansas. The study consisted of two N management treatments: Normal (single N application as UAN using broadcast nozzles with the absence of urea inhibitors); and Progressive (split N application into two timings using streamer bars with urease inhibitors). Both treatments had similar results in all variables measured at Hutchinson, which was the lowest yielding location. In Ashland Bottoms, the number of heads/ft2and total aboveground biomass did not differ significantly between the treatments. However, grain yield, grain test weight, and protein content were significantly greater in the progressive N management. These results demonstrate the enhanced N use efficiency (NUE) of progressive N management in higher-yielding environments by better N allocation in the plant. This research demonstrates that it is possible to increase both grain protein content and grain yield in high rainfall areas without extra amounts of N fertilizer.
Keywords: Triticum aestivum L.; wheat; nitrogen; urease inhibitor; protein